2020
DOI: 10.18805/lr-4330
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Profenofos Residues using LC-MS/MS and Its Dissipation Kinetics in Pigeonpea Pods

Abstract: Background: Pigeonpea is a drought resistant legume crop, cultivated in semiarid tropical and subtropical regions of the world mainly for its protein enriched seeds. Insect pests are major biotic constraints implicating yield losses of staggering dimensions. Profenofos is being used for management of pigeonpea pod borer and studying the pattern of dissipation, residual occurrence and hazard index for consumption of pigeonpea grain contaminated with profenofos is very important. Methods: A simple, sensitive and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(5 citation statements)
references
References 13 publications
2
3
0
Order By: Relevance
“…The uncertainty values associated with the method for Capsicum and tomato matrices was found acceptable. Similar results observed with estimation uncertainty during analysis of spent leaves, made tea and tea infusion was found acceptable for most of the pesticides and it indicated that the method has high sensitivity and is suitable for multi-residues analysis [ 41 , 43 ] and results are in accordance with estimation of uncertainty in a pigeonpea matrix analyzed with GC-MS/MS and LC-MS/MS [ 33 ].…”
Section: Resultssupporting
confidence: 69%
See 3 more Smart Citations
“…The uncertainty values associated with the method for Capsicum and tomato matrices was found acceptable. Similar results observed with estimation uncertainty during analysis of spent leaves, made tea and tea infusion was found acceptable for most of the pesticides and it indicated that the method has high sensitivity and is suitable for multi-residues analysis [ 41 , 43 ] and results are in accordance with estimation of uncertainty in a pigeonpea matrix analyzed with GC-MS/MS and LC-MS/MS [ 33 ].…”
Section: Resultssupporting
confidence: 69%
“…The present method was in accordance with the methods developed for determination of pesticides residues in pepper was found acceptable interms its accuracy, repeatability and reproducibility [ 13 , 26 , 27 , 28 ]; analysis of tricyclazole in rice with lowest detection level (0.002 μg g –1 ) was achieved and could be useful for monitoring of rice samples subjected to export [ 29 ]; chlorantraniliprole, indoxacarb and profenofos analysis in pigeonpea following a method standardized through LC-MS/MS with lowest detection and quantification level [ 30 , 31 , 32 ] and multiple residues in pigeonpea [ 33 ]. Pyridaben analysis in unprocessed and processed peppers [ 13 ] and etoxazole [ 34 ] are promising methods to identify and quantify the corresponding residues.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Six ( 6) VOCs (isoprene, toluene, cumene, polyvinyl alcohol, carbontetrachloride, chloroform) were detected in the raw 'moi-moi' paste and upon cooking, all showed a decrease in concentration at day O. However, polyvinyl alcohol, carbontetrachloride, chloroform and toluene showed increase in their concentrations on day 3 while benzene and myrcene which were not originally in the raw 'moi-moi' paste were detected in the cooked 'moi-moi' on day 3 This further underlines the reports that migrations from food packages into the packaged food increases with increase in contact time [1,33,34]. Isoprene has been listed on the US Hazardous Substance fact sheet [35] as one of the volatile organic compound posing a health risk to humans upon exposure and since it is carcinogenic, there is no maximum limit of exposure.…”
Section: Volatile Organic Compounds (Vocs)supporting
confidence: 65%